The effective role of ascorbic acid in the photoelectrocatalytic reduction of CO2 preconcentrated on TiO2 nanotubes modified by ZIF-8 - Cardoso, J. C.; Stulp, S.; de Souza, M. K.R.; Hudari, F. F. [UNESP]; Gubiani, J. R.; Frem, R. C.G. [UNESP]; Zanoni, M. V.B. [UNESP] (Elsevier, 2020)
This work is aimed at investigating the effects of ascorbic acid as sacrificial agent in the photoelectrocatalytic reduction of CO2 to alcohol. The results show that the addition of electron donor agent (0.2 mol L−1 ascorbic acid) to the electrolyte (0.1 mol L−1 sodium sulfate pH 4.5) led to an improvement of 22% and 12% in CO2/methanol and CO2/ethanol conversion respectively, after 3 h of photoelectrolysis conducted on TiO2 nanotubes decorated with ZIF-8 nanoparticles under Eapp = 0.1 V and UV–Vis irradiation. The photoelectrocatalytic results were compared with photocatalytic, photolytic and electrocatalytic performance. The findings of this work unfold an interesting perspective for the use of sacrificial agent in photoelectrocatalysis and the generation of products of great energetic value from pollutants that cause environmental degradation in systems carried out under constant pressure and low temperature.
Keywords: Electron donor agent; Ethanol; Methanol; Photocatalyst; Photoelectrocatalysis